Spin Wheel Based Graphical Password Authentication Resistant to Peeping Attack - Kameswara Rao, M; S.G. Santhi, Dr; Md.Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
Gadgets outfitted with touch screens rule the present versatile market in view of high adaptability and great convenience. Numerous security applications keep running on such gadgets. For user verification recalling or recognizing a secret word is testing errand in touch screen based gadgets. A graphical based secret key is a standout amongst the most encouraging and upcoming option for touch based devices. As per research, human brain can recall pictures more effectively than content. In this paper we introduce a novel spin wheel based authentication system targeting the touch screen based versatile and handheld gadgets. The user needs to rotate a set of spin wheels to get authenticated .Usability Study was directed to investigate the ease of use and security of the proposed authentication mechanism.